2020
DOI: 10.1002/jsfa.10615
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography with fluorescence detection fingerprints as chemical descriptors to authenticate the origin, variety and roasting degree of coffee by multivariate chemometric methods

Abstract: BACKGROUND Coffee is one of the most popular beverages around the world, consumed as an infusion of ground roasting coffee beans with a characteristic taste and flavor. Two main varieties, Arabica and Robusta, are produced worldwide. Furthermore, interest of consumers in quality attributes related to coffee production region and varieties is increasing. Thus, it is necessary to encourage the development of simple methodologies to authenticate and guarantee the coffee origin, variety and roasting degree, aiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Besides the availability of more efficient industrial plants and the parallel increased potentiality of data recording and process monitoring, a big improvement in cropping, selection, processing, roasting and extraction processes has been done, leading to a quick development in the SC sector. Many studies on these topics indeed are aimed to evaluate quality indicators and to assess the authenticity of raw material (Maeztu et al ., 2001; Piccino et al ., 2014; Toci & Farah, 2014; Zhang et al ., 2019; Wadood et al ., 2020; Núñez et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the availability of more efficient industrial plants and the parallel increased potentiality of data recording and process monitoring, a big improvement in cropping, selection, processing, roasting and extraction processes has been done, leading to a quick development in the SC sector. Many studies on these topics indeed are aimed to evaluate quality indicators and to assess the authenticity of raw material (Maeztu et al ., 2001; Piccino et al ., 2014; Toci & Farah, 2014; Zhang et al ., 2019; Wadood et al ., 2020; Núñez et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [14,15,20], we have demonstrated that HPLC-UV and HPLC-FLD fingerprints obtained after simply brewing coffees resulted in good sample chemical descriptors to address coffee classification regarding their production region, variety, and roasting degrees. This contribution aims to assess coffee authenticity when dealing with adulterations involving the use of common non-coffee-based adulterants relying on an untargeted fingerprinting strategy.…”
Section: Hplc-uv and Hplc-fld Fingerprintsmentioning
confidence: 98%
“…Is for these reasons that food quality control of commercial coffee products to ensure coffee authenticity and to protect the consumers is very important [6,[10][11][12].Both targeted and untargeted analytical strategies have been described in the literature to address the discrimination, classification, and authentication of coffee samples based on the coffee region of production, their variety or their roasting degree. Some examples rely on liquid chromatography (LC) with ultraviolet (UV) [13,14] and fluorescence detection (FLD) [15], or LC [16], gas chromatography [17,18] and direct analysis in real-time (DART) [19] with mass spectrometry. However, in the last years, several works have been focused on the study of coffee adulteration cases either with coffees of inferior quality [14,15,20] or with different products such as chicory, corn, barley or wheat, among others [7][8][9][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations